Relational contracts: Public versus private savings - Francesc Dilmé; Daniel F. Garrett (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Work on relational employment agreements often predicts low payments or termination for poor performance. The possibility of saving can, however, limit the effectiveness of monetary incentives in motivating an employee with diminishing marginal utility for consumption. We study the role of savings and their observability in optimal relational contracts. We focus on the case where players are not too patient, and hence the constant first-best effort cannot be implemented. If savings are hidden, the relationship eventually deteriorates over time. In particular, both payments and effort decline. On the other hand, if savings are public, consumption is initially high, so the agent's savings fall over time, and effort and payments to the agent increase. The findings thus suggest how tacit agreements on consumption can forestall the deterioration of dynamic relationships in which the agent can save.
Keywords: C73; J30; 330; relational contracts; consumption smoothing preferences; private savings